Characteristics of sludge-based pyrolysis biochar and its application of enhancing denitrification. (December 2022) - Tong, Huiyan; Duan, Zhenghang; Yang, Xin; Li, E.; Liu, Yiding; Zhou, Hao; Zhang, Xuwang; Yang, Xiaojing; Xu, Weiping
Abstract: A modified biochar for enhanced denitrification was developed through a facile pyrolysis method using sewage sludge as raw material and melamine as nitrogen source. Through electrochemical analysis, sludge-based pyrolysis biochar (SPBC) has superior electrical conductivity and poor redox activity. SPBC can increase the electron transfer through the geoconductor mechanism. The effect and the mechanism of SPBC on denitrification were studied. The nitrate treatment efficiency increased with the increase of SPBC dosage. From the perspective of molecular biology, the activities of NAR and NIR enzymes, the degradation efficiency of glucose and the ETSA of bacteria were all promoted with the increase of SPBC, thereby promoting the removal of NO3 − . In addition, SPBC had a certain screening effect on microbial communities, and biodiversity decreased with the increase of SPBC dosage. Although the biodiversity decreased, the relative abundance of microorganisms conducive to denitrification increased with the increase of SPBC dosage. The transformation strategy of SPBC proposed in this paper provides a technical solution for sludge recycling and application for strengthening denitrification. Graphical abstract: Image 1 Highlights: SPBC for enhanced denitrification was obtained through a facile pyrolysis method. SPBC has superior electrical conductivity, which can be used as a geoconductor. SPBC promotes denitrification by enhancing ETSA, NAR and NIR enzymes activities. SPBC has a screening effect on certain bacteria in denitrification. SPBC mainly increases the denitrification rate through the geoconductor mechanism.